INNOVATIVE LEADERSHIP OF EARLY CHILHOOD EDUCATION ADMINISTRATORS IN THE 21st CENTURY - Kongkaphan , Chanyanat (Journal of Educational Review Faculty of Education in MCU, 2025)
This article aimed to present the innovative leadership of early childhood education administrators in the 21st century. The study revealed four key dimensions of innovative leadership: 1) innovative vision, 2) innovative thinking, 3) innovative atmosphere creation, and 4) innovation management. Moreover, critical success factors in developing innovative leadership were identified, including administrator competency development, creation of innovation ecosystems, and continuous assessment and development. The knowledge synthesis was conducted using a three-level analytical framework: theoretical, policy, and practical levels, through thematic analysis. The findings led to the presentation of a conceptual framework for developing innovative leadership appropriate for the early childhood education context in Thailand, covering individual innovative competency development, innovation ecosystem development in educational institutions, and continuous assessment and development of innovative leadership. However, effective and sustainable development of innovative leadership required ecological system integration and sustainability in development, which presented significant challenges for driving Thai early childhood education in the 21st century.